THE ROLE OF TAX AUDITS AS A MODERATOR OF TAX AVOIDANCE IN INDONESIA - Budiman, Nita Andriyani; Susanti, Diah Ayu (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to investigate the role of tax audits in moderating the effects of transfer pricing, tax haven, and institutional ownership on tax avoidance. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 with a total of 325 observations. The results show that transfer pricing has a positive impact on tax avoidance, while tax havens does not have a significant effect. In contrast, institutional ownership is found to have a negative effect on tax avoidance. Additionally, tax audits are shown to weaken the positive impact of transfer pricing on tax avoidance, but they are not effective in moderating the effects of tax haven usage or institutional ownership. These findings offer valuable insights for tax authorities, helping them prioritize audits and monitoring efforts based on transfer pricing documentation in various sectors. Furthermore, the study highlights the importance of tax auditors fully utilizing the Automatic Exchange of Information (AEoI) to strengthen oversight of cross-border transactions involving affiliated companies.